2020
DOI: 10.3389/fpsyg.2020.00579
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Personal and Social Responsibility Model as a School-Wide Project in All Participants: Teachers’ Views

Abstract: The present study aims to apply a program based on Hellison's Teaching Personal and Social Responsibility Model (TPSR), traditionally used in Physical Education, to other educational participants and examine the assessment of the teachers who carried it out during the 2018-2019 school year. The program was applied over 8 months of one academic year and during at least 60% of the weekly class hours. Initially, 30 teachers participated, of whom 16 were involved in the interviews carried out, all of them being Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 27 publications
1
23
0
3
Order By: Relevance
“…Taking SDT as a reference and in line with Vallerand's hierarchical model, it can be observed that applying hybrid methodologies that manipulate social factors, such as responsibility, are suitable for producing an improvement in basic psychological needs and promoting a more self-determined motivation [19], generating positive consequences at an affective and emotional level, such as enjoyment and the intention to be physically active, in line with the studies by Manzano-Sánchez et al [54], Menéndez-Santurio and Fernández-Río [90], and Merino-Barrero et al [24].…”
Section: Discussionmentioning
confidence: 99%
“…Taking SDT as a reference and in line with Vallerand's hierarchical model, it can be observed that applying hybrid methodologies that manipulate social factors, such as responsibility, are suitable for producing an improvement in basic psychological needs and promoting a more self-determined motivation [19], generating positive consequences at an affective and emotional level, such as enjoyment and the intention to be physically active, in line with the studies by Manzano-Sánchez et al [54], Menéndez-Santurio and Fernández-Río [90], and Merino-Barrero et al [24].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the lack of improvements in the motivation variable that have been reported could be due to the short time of the intervention. There are several studies which alluded to the lack of time during the implementation for the program as the main reason why no significant changes are achieved in the variables studies [54,59,60], despite the fact that for teachers who implement this new program, it is motivating [61]. However, in this research, the intervention program lasted a whole school year, so other factors such as the kind of motivation measured (PE motivation versus academic motivation), instruments used (questionnaire to assess motivation in the PE class or perceived locus of causality versus EME) [62,63], or the sample size could be behind these results [53].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed positive results after the implementation of TPSR in schools, not only in variables such as motivation, responsibility, or autonomy, but also in the classroom climate among primary and secondary school students [ 12 ]. Furthermore, this methodology is considered suitable for teachers from different subjects and useful for teaching values and improving their lessons, with teamwork between teachers being essential [ 13 ]. Therefore, the promotion of responsibility could contribute to the improvement of other factors such as resilience, prosocial behaviour, the perception of violence, and, consequently, classroom climate, factors that have been considered in various studies, as can be seen in the reviews [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%